Analisis Kontribusi Pendapatan Usahatani Padi Sawah terhadap Pendapatan Rumah Tangga Petani di Desa Kalimbu Kuni Kecamatan Kota Waikabubak Kabupaten Sumba Barat - Sania Louru Todu; Elsa Christin Saragih (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2026)
The analysis in this study was conducted to calculate income from rice farming, as well as measure the contribution of rice paddy income to total household income in Kalibu Kuni Village. The research area was determined by purposive sampling method, which was deliberately selected in Kalibu Kuni Village, because it is one of the villages that produces rice every year. This activity took place in two months, starting from April 2026 to May 2026. Eighty-three rice farmers in Kalibu Kuni Village participated as respondents in this study. To determine the average income from rice farming in Kalibu Kuni Village, Waikabubak City District, West Sumba, an agricultural income analysis was conducted. To obtain the total income of farmer households, the total income from rice cultivation, agricultural income other than rice, and income from the non-agricultural sector was added up. Then, an analysis of the contribution of income from rice cultivation to the household income of rice farmers in Kalibu Kuni Village was conducted. The results of the analysis showed that the average income from rice cultivation was Rp 49,510,908.43 per year. The average household income of respondents in this study was Rp. 61,359,101.35 per year, where with a contribution of 80.69% from rice cultivation, it can be concluded that rice cultivation makes a high contribution to the household income of farmers in Kalimbu Kuni Village.